Stakeholders' perspectives and use of web-based knowledge support for environmental information on pharmaceuticals - Elkanah Linder; Johanna Villén; Marmar Nekoro; Björn Wettermark; Sofia Kälvemark Sporrong (Elsevier, 2023)
Background: Pharmaceuticals treat and prevent diseases but can pose a risk to organisms, predominantly in aquatic environments. The use of pharmaceuticals is predicted to increase due to, among other factors, a growing and aging population and climate change. Therefore, it is important to develop mitigation strategies to prevent pharmaceutical residues from entering the environment. In Sweden, two public pharmaceutical web-based knowledge supports provide information on the environmental impact of pharmaceuticals. Objective: To explore stakeholder perspectives, use and future opportunities related to two webbased knowledge supports publicizing environmental information on pharmaceuticals. Methods: Stakeholders identified for their experience with the knowledge supports, pharmaceutical policy, and stakeholder collaboration were recruited using purposive and snowball sampling for semi-structured interviews. Interviews were conducted in person or via video calls. Respondents included twenty-one representatives from the pharmaceutical industry, regional and national authorities, academia, and an independent research institute. Interview transcripts were analyzed using content analysis. Results: Respondents valued having environmental information on pharmaceuticals publicly accessible on two well-known pharmaceutical knowledge supports. The knowledge supports have been used in Sweden and internationally. Perceived differences were recognized between the impact and perspectives of the two knowledge supports with a general preference for the Janusinfo knowledge support. The preference was especially identified regarding transparency and the use of the information in clinical practice. Barriers to impact were a lack of resources and decision-making criteria. Respondents believed that the impact and value of the knowledge supports could be improved with more authority involvement. Conclusion: Public knowledge support providing environmental information on pharmaceuticals has been valuable across sectors, especially, among Drug and Therapeutics Committees. We believe the results from this study could be useful for other countries interested in implementing a similar system.